A side-chain engineering approach to solvent-resistant semiconducting polymer thin films. Issue 3 (30th November 2015) - Guo, Zi-Hao; Ai, Na; McBroom, Connor Ryan; Yuan, Tianyu; Lin, Yen-Hao; Roders, Michael; Zhu, Congzhi; Ayzner, Alexander L.; Pei, Jian; Fang, Lei
Abstract : Latent H-bonds in conjugated statistical copolymers rendered semiconducting thin films resistant to solvent immersion. Abstract : Side-chain manipulation of isoindigo-thiophene derived conjugated polymers was achieved by statistical copolymerization of two different isoindigo monomers decorated with t -Boc groups and polyisobutylene chains, respectively. The long polyisobutylene side-chains ensured solution-processability of the polymers while the t -Boc groups served as a cleavable H-bond inhibitor. By post-film-casting thermal treatment, the t -Boc groups could be removed efficiently to generate a H-bond cross-linked polymer network, which demonstrated excellent solvent resistance. Organic field-effect transistor devices made from these thin films demonstrated retained electronic properties after being immersed in organic solvents. By taking advantage of the post-annealing solvent resistant feature, multilayered films of the polymers could be fabricated using multiple "casting–annealing–casting–annealing" cycles.